Aspects of Immobilisation of Catalysts on Polymeric Supports - Dioos, Bart M. L.; Vankelecom, Ivo F. J.; Jacobs, Pierre A. (Advanced synthesis & catalysis, 2006)
In this review the authors intend to make a tutorial review on catalyst immobilisation from the viewpoint of the catalyst designer, emphasizing the use of promising concepts in this area, rather than trying to be exhaustive. The following topics are covered: